PEMBIMBINGAN PEMBUATAN DAN UJICOBA MESIN BRIKET ABU ARANG PADA WARGA SAPTORENGGO, PAKIS, MALANG - Purwoko Purwoko; Santoso Santoso; Syamsul Hadi; Eko Yudiyanto; R.N. Akhsanu Takwim (Jurnal Pengabdian kepada Masyarakat, 2025)
The problem lies in the lack of empowerment of residents in making Charcoal Ash Briquette Machine and their trials. This community service activity aims to guide residents of Saptorenggo, Pakis, Malang in making and testing effective Charcoal Ash Briquette Machine. The method applied is a discussion with residents in the design of the Charcoal Ash Briquette Machine with the working principle of pressing with a rolling roller on a mold plate, making the machine using available and affordable technology, assembly, and testing. The results of community service are in the form of a Charcoal Ash Briquette Machine with a capacity of 45 kg / hour with cylindrical briquette products with a diameter of 8 mm or 12 mm through collaboration between residents of Saptorenggo, Pakis, Malang and the State Polytechnic of Malang (Polinema), so that synergy is established between Polinema and residents of Saptorenggo, Pakis, Malang in producing briquettes from effective wood charcoal ash.